2020
DOI: 10.3389/fphar.2020.585612
|View full text |Cite
|
Sign up to set email alerts
|

Linagliptin Regulates the Mitochondrial Respiratory Reserve to Alter Platelet Activation and Arterial Thrombosis

Abstract: Background: The pharmacological inhibition of dipeptidyl peptidase-4 (DPP-4) potentiates incretin action, and DPP-4 is a drug target for type 2 diabetes and reducing cardiovascular risk. However, little is known about the non-enteroendocrine pathways by which DPP-4 might contribute to ischaemic cardiovascular events.Methods: We tested the hypothesis that inhibition of DPP-4 can inhibit platelet activation and arterial thrombosis by preventing platelet mitochondrial dysfunction and release. The effects of pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…L-NAME treatment began two weeks before LPS injection. Linagliptin treatment (5 mg/kg/day) was administered by oral gavage [ 37 ] for 2 days prior to LPS injection. LPS (10 mg/kg) purified from Salmonella typhosa was administered by single intraperitoneal injection 24 h before the end of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…L-NAME treatment began two weeks before LPS injection. Linagliptin treatment (5 mg/kg/day) was administered by oral gavage [ 37 ] for 2 days prior to LPS injection. LPS (10 mg/kg) purified from Salmonella typhosa was administered by single intraperitoneal injection 24 h before the end of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…PRP was counted by Hematology Analyzer to adjust platelet density at 300 × 10 9 per sample. After the stimulation of ADP (Helena Laboratories, USA), platelet aggregation was analyzed with a turbidimetric aggregation-monitoring device (Helena Laboratories, Beaumont, TX, United States) according to previously report (Li et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…DPP-4i have also been demonstrated to increase the mobilization and activity of circulating endothelial progenitor cells (EPCs), which play a crucial role in angiogenesis and endothelial repair [22]. Finally, several clinical and pre-clinical studies indicated the anti-thrombotic effects of DPP-4i mediated by mechanisms such as attenuation of mitochondrial respiration and thrombin-induced aggregation, increased intracellular cyclic AMP levels improving NO availability, inhibitory effects on tyrosine phosphorylation and intracellular free calcium [137,147,148].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%